Redirecting pedicle screws: a revision spinal fusion strategy using three‐dimensional image guidance. Issue 4 (12th January 2016) - Yoon, Jang W.; Nottmeier, Eric W.; Rahmathulla, Gazanfar; Fenton, Douglas S.; Pirris, Stephen M.
Abstract: Background: Pedicle screws are a preferred method for spinal fixation because of their three‐column support and rigid posterior stabilization. The purpose of this study was to evaluate the outcome of patients requiring pedicle screw redirection, and to describe a technique using cone‐beam computed tomography (cbCT). Methods: A retrospective review of 30 patients undergoing revision spinal fusion with redirection of pedicle screws was performed. Fifty pedicle screws were redirected in these patients using cbCT‐based 3D image guidance. They were graded pre‐ and post‐operatively using an established grading system. Results: No complications occurred in this study as a result of redirection. No pedicle breach was noted in all of the redirected pedicle screws. Conclusion: Redirection of misplaced pedicle screws using cbCT‐based 3D image guidance seems to be safe and accurate in our experience. Further studies are needed to establish its safety, accuracy, fusion rate, and clinical outcome compared with other methods. Copyright © 2016 John Wiley & Sons, Ltd.